Altered axonal excitability properties and nerve edema in POEMS syndrome. Issue 10 (October 2015) - Mitsuma, Satsuki; Misawa, Sonoko; Shibuya, Kazumoto; Isose, Sagiri; Sekiguchi, Yukari; Iwai, Yuta; Beppu, Minako; Watanabe, Keisuke; Amino, Hiroshi; Kuwabara, Satoshi
Highlights Axonal excitability and its correlation with serum VEGF and nerve edema detected by ultrasound were studied in POEMS syndrome. Excitability testing suggested possibly altered sodium, potassium, and inward rectifying currents, some of which were correlated with VEGF levels and nerve edema. In addition to structural changes (demyelination), nerve edema induced by upregulated VEGF, and upregulated inflammatory cytokines can modulate profiles of POEMS neuropathy.